Safety guaranteed longitudinal motion control for connected and autonomous vehicles in a lane‐changing scenario - Hu, Zhanyi; Yang, Zeyu; Huang, Jin; Zhong, Zhihua (IET intelligent transport systems, 2021)
This paper aims at utilising the ideology of controlling a constrained dynamical system to address the longitudinal motion control problem during lane‐changing process subject to time‐varying uncertainties. To this end, a robust controller is designed based on Udwadia–Kalaba (UK) approach and Lyapunov stability theory. Most of the studies on lane‐changing considered only the equality constraint, namely the desired inter‐vehicle distance. In a bilateral inequality constraint, the upper bound avoids unpredictable cut‐ins and the lower bound collisions. This research applies the constraint to guarantee a safe and efficient lane‐changing process. The original UK approach cannot handle bilateral inequalities. Therefore, a diffeomorphism method is proposed to transform the bounded state to an unbounded one. The latter enables the UK approach to deal with both equality and bilateral inequality constraints. The proposed controller can render each vehicle to adjust its distance with the predecessor without violating the prescribed bounds. Numerical experiments have been conducted to validate the effectiveness of the proposed controller under different traffic demands.